Down syndrome incidence during 2007-2012 on Gynaecology and obstrtrics clinic Clinical center Kragujevac - Dimitrijević, Aleksandra Slavoljub (Medicinski časopis, 2012)
During four year period, between January 2007 and December 2011, 8 cases of Down syndrome were diagnosed by amniocentesis of 1208 amnions, which results us incidence of 1 in 151 amnions, also we had 15 cases of liveborn children with Down syndrome in 10822 liveborn babies, which makes an incidence of 1 in 721 liveborns. 1070 pregnancies were with mothers older then 35 years at the time of labor and 5 of 15 live born babies with Down syndrome are from mothers in this group. Also, 9464 pregnancies were with mothers of age 18-35 years and in this group we have 10 cases of Down syndrome. Only 9,99% of all mothers were older then 35 years, and they  participated in 33.3% of all Down syndrome. Young mothers had 18-35 years we have 88.3% of all mothers and they participated with only 66,7% children with Down syndrome.     We had 8 fetuses with Down syndrome, all diagnosed with trisomy 21, all were aborted by choice of parents and Ethical committee of Clinical Center Kragujevac.   Decision of not having prenatal diagnostics for pregnancies, some by late amniocentesis, some by decision of the family resulted in Down syndrome  liveborns.